2011
DOI: 10.1371/journal.pone.0024548
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Malaria, Birth Size and Blood Pressure in Nigerian Newborns: Insights into the Developmental Origins of Hypertension from the Ibadan Growth Cohort

Abstract: BackgroundHypertension is an increasing health issue in sub-Saharan Africa where malaria remains common in pregnancy. We established a birth cohort in Nigeria to evaluate the early impact of maternal malaria on newborn blood pressure (BP).MethodsAnthropometric measurements, BP, blood films for malaria parasites and haematocrit were obtained in 436 mother-baby pairs. Women were grouped to distinguish between the timing of malaria parasitaemia as ‘No Malaria’, ‘Malaria during pregnancy only’ or ‘Malaria at deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
2
16
2
Order By: Relevance
“…Even with recruitment at the immunisation clinic, we were able to recruit only a small proportion of this category of mothers. Despite the baseline underrepresentation of mothers giving birth at home, the distribution of newborn anthropometric measurements was consistent with other Nigerian studies and INTERGROWTH-21 [40][41][42][43]. In the sub-study, we observed that the women giving birth at home were less educated and displayed lower utilisation of maternal health services including antenatal care, attendance by health professional during delivery and postnatal family planning.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Even with recruitment at the immunisation clinic, we were able to recruit only a small proportion of this category of mothers. Despite the baseline underrepresentation of mothers giving birth at home, the distribution of newborn anthropometric measurements was consistent with other Nigerian studies and INTERGROWTH-21 [40][41][42][43]. In the sub-study, we observed that the women giving birth at home were less educated and displayed lower utilisation of maternal health services including antenatal care, attendance by health professional during delivery and postnatal family planning.…”
supporting
confidence: 87%
“…We assessed the external validity of the anthropometric measurements for the pilot KID Birth Cohort Study by comparing with standards of other Nigerian studies and INTERGROWTH-21 (Table S2). [40][41][42][43] The sub-study participants included individuals listed in CEGROMS at 22 months of the pilot study (October 2018) and have a phone number. Risk difference (RD) was used to assess the association of baseline maternal characteristics and participation in the sub-study.…”
Section: Discussionmentioning
confidence: 99%
“…Weight SDS <−1 occurred in 42% and 53%, and length SDS <−1 in 36% and 37% at birth and 12 months, respectively. Mean birth anthropometry and SDSs of all malaria-exposed infants, sexes combined, were globally and significantly smaller than those not exposed (as detailed previously) 14 but differed (Table 1). At 12 months, these effects persisted in boys.…”
Section: Anthropometry Growth and Bp By Sex And Effect Of Maternal supporting
confidence: 54%
“…54 Four papers from Southern Africa were from the same cohort but presented data on BP at different ages of follow-up. [46][47][48][49] Four papers reported results in neonates (0-28 days), 41,43,44,51 four in children (1-9 years), 39,40,49,55 four in adolescents (10-19 years) 42,47,48,54 and four in both children and adolescents. 45,46,52,53 The papers were published between 1989 and 2016.…”
Section: Resultsmentioning
confidence: 99%